MYTH AND SYMBOLS IN WOLE SOYINKA'S IDANRE - Migliavacca, Adriano Moraes (Cadernos do IL, 2017)
Poetry and mythology are narrowly associated. In the various civilizations poetry originates in oral form from mythology, acquiring its first written realization in the narrative or epic poem. Although it has distanced itself from its narrative origins, many writers in the Twentieth Century have reaffirmed myth and narrative in poetry. Among them, the Nigerian poet and playwright Wole Soyinka stands out, whose works both in drama and poetry are largely inspired by Yoruba mythology. An example of this is the narrative poem Idanre, which provides an account of the creation myth of Ogun, Yoruba god of iron, culture and creativity, set in modern times. This study is an investigation and discussion of the presence of myth and symbols associated to it in the poem and their specific realization in Yoruba mythology.